Growth strategy as a mediator of the relationship between entrepreneurial competencies and the performance of SMEs - Endi Sarwoko (Universitas Hayam Wuruk Perbanas, 2016)
Factors affecting the success of SMEs have been widely studied, but generally they only focus on the individual characteristics as a factor affecting the success of SMEs. This study attempts to analyze the role of the growth strategy in mediating the effect of entrepreneurial competencies on SMEs performance. The population consists of the 243 nurturing SMEs in Malang Regency, in which the sample was taken using proportional sampling techniques, and it was totaled 146 SMEs. They were collected by using questionnaires and interviews, whereas analytical techniques using Structural Equation Modeling. The results showed that the growth strategy is influenced by entrepreneurial competencies, so the business growth strategy, as a mediator of the effect of entrepreneurial competencies on SMEs performance, meaning that the increase of the entrepreneurial competencies will lead to a higher capability implementing the growth strategy. This eventually affects the SMEs performance. Entrepreneurial competencies will affect the better business growth strategy. In turn, it can also ultimately improve SMEs performance. Thus, the key factor in the SMEs performance in Malang Regency is the level of competency owned by the owners and the implementation of growth strategy.Â